Women's participation on the boards of farmer-owned cooperatives - Hansen, Henning Otte; Asmild, Mette (Frontiers in Veterinary Science, 2023)
Initiatives and specific measures aimed at increasing the presence of women on corporate boards have become widespread. However, not much academic attention has been paid to this subject up till now, when it comes to farmer-owned cooperatives. The article shows that farmer-owned cooperatives do have special problems when it comes to women on boards. The farmer-owned cooperatives in Denmark have been chosen as cases in this article, as they are quite big, exposed to international competition and have substantial market power. Based on annual reports from 25 farmer-owned cooperatives and two of their investor-owned subsidiaries in the years 2005-2022, inputs from present and former board members of farmer-owned cooperatives, CSR-reports etc. a number of conclusions are drawn: Cooperatives have particular challenges with regard to gender diversity on boards due to their specific structure and requirements compared to investor-owned companies. Different types of barriers that limit women's representation on boards can be identified: • Institutional barriers in terms of statutes and cooperative principles • Structural barriers in the form of a narrow or skewed recruitment base • Historical and cultural barriers, where agriculture is typically a male-dominated business. Women's representation on boards of farmer-owned cooperatives is relatively low but increasing. From 2005 to 2021 the weighted average share of female board members has increased from about 1 to 20 percent. Gender diversity in farmer-owned cooperatives is consistently less than in listed companies. The increasing representativeness of women is primarily due to the presence of more female external members. Since 2013 the proportion of women has increased, and in 2021 there were more female than male external board members. Female board members are more common in the large farmer-owned cooperatives than in the small. A positive correlation between the size of the companies and the representation of women is identified. This is supported by large cooperatives' greater focus in annual reports and CSR strategies on women's representativeness. Based on the cooperatives' diversity policy, their explicit and specific goals for women's representativeness on boards, interviews with board members etc. a clear awareness of the challenge of gender diversity on the boards is identified.